Mapping Dairy Farmers’ Preferences for Improved Feeding Practices Using Paired Comparison Method - Shruti; Yadav, Shivam; Singh, Madan; Kala, Anju; Verma , Harideep; Choudhary, Khushboo (Indian Journal of Extension Education, 2025)
Dairy farmers’ preferences for improved feeding practices were assessed in Bareilly district of Uttar Pradesh using a pairwise comparison technique. The findings indicate a strong preference for traditional, low-cost interventions. Salt supplementation ranked highest with a scale value of 2.924, followed by year-round green fodder production (2.730) and sugarcane tops (2.281). These results highlight farmers’ favour for easily accessible and cost-effective options. Moderately accepted practices included mineral mixtures (1.862) and fresh vegetable waste (1.787), reflecting a cautious openness. However, more scientifically advanced practices such as anti-methane additives, probiotics, bypass fat, hay, urea-treated straw, and silage were less preferred, with scale values ranging from 1.325 to near zero. This lower acceptance suggests either limited awareness or reluctance to adopt more technical and potentially costly feeding practices. To evaluate the consistency of these preferences, an internal consistency check was conducted. The resulting average discrepancy of 0.090 indicates a reasonable level of internal consistency. Overall, the findings provide a clear picture of current dairy feeding practice preferences, with traditional approaches continuing to dominate farmer choices.